L’asile contre la santé ? Vie et mort des homosexuels sénégalais réfugiés en Mauritanie - Christophe Broqua; Gabrièle Laborde-Balen; Agathe Menetrier; Djamil Bangoura (L’Année du Maghreb)
In Senegal, where acts “against nature with an individual of the same sex” are punishable by prison, gay men live in fear of denunciation and are regularly victims of violence and discrimination. This situation, which has worsened year after year since the end of the 2000s, has led them to seek exile in neighboring countries. In Mauritania, some obtain refugee status from the United Nations High Commissioner for Refugees (UNHCR) and sometimes “resettlement” in Europe or North America after a long administrative process awaited in doubt. Many of the asylum seekers in Nouakchott are infected with HIV and some are dying from it despite the free availability of antiretroviral treatment. This article analyzes the circumstances that contribute to the deterioration, sometimes lethal, of the health conditions of some Senegalese gay men in exile in Mauritania. It appears that not only does the asylum system fail to ensure the safety and health of all those who rely on it, but it also exposes them to increased health risks that sometimes lead to death.